EXPLORATION OF THE ROLE OF ARJA BASUR AS A MEDIA FOR COMMUNICATION OF HINDU VALUES: CASE STUDY OF BUALU BADUNG TRADITIONAL VILLAGE - Ni Luh Novayanti, (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
Arja Basur is a form of traditional Balinese theater that combines elements of dance, drama, and music into a captivating performance. The beauty of the dance movements, the depth of the narratives, and the distinctive accompaniment of traditional Balinese music have become integral parts of the life of the Balinese people, particularly in Desa Adat Bualu, South Kuta District, Badung Regency. Arja Basur is rich in Hindu philosophical values, conveyed through dialogue, song lyrics, and symbolism within the performance. This makes Arja Basur an effective communication medium for conveying Hindu values to the community. The research questions formulated in this study are: How does the Arja Basur dance-drama exist in Desa Adat Bualu, Badung, Bali? How is Arja Basur used as a medium to communicate Hindu values in Desa Adat Bualu? What Hindu values are embodied in the Arja Basur performances in Desa Adat Bualu? The theoretical framework employed includes Carey's (2009) ritual communication theory and Schechner's (2013) concept of theater as a communication medium. This study is designed using a descriptive qualitative research methodology. Data collection methods include interviews, literature studies, and documentation. The Arja Basur dance-drama in Desa Adat Bualu, Badung, is sacred and is regularly performed traditionally every Saturday Kliwon Wuku Kuningan at Pura Dalem Lamun. The Arja Basur performance in Desa Adat Bualu, serves as a communication medium that conveys Hindu values, including the aims of Hinduism, Tri Kaya Parisudha, Asta Brata, Rwa Bhineda, Tri Hita Karana, Catur Purusa Artha, Panca Sraddha, Tri Guna, and ethics.